1998
DOI: 10.1016/s0014-5793(98)01011-4
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor‐binding protein‐2 inhibits proliferation of human embryonic kidney fibroblasts and of IGF‐responsive colon carcinoma cell lines

Abstract: So far, the physiological role of insulin-like growth factor binding protein-2 (IGFBP-2) has not been demonstrated directly. Therefore, we transfected 293 cells with an expression vector containing the CMV promoter and the complete cDNA of mouse IGFBP-2. Secretion of bioactive IGFBP-2 into conditioned medium was demonstrated by Western ligand and Western immunoblotting and quantified by specific RIA. For the analysis of cell proliferation three clones exhibiting either high or low/no IGFBP-2 expression were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 63 publications
(48 reference statements)
2
51
0
Order By: Relevance
“…A reduction in IGFBP-2 and IGFBP-4 in response to changes in local cytokine concentrations could alter the process of maturation of the enterocyte moving from the crypt to the apex of the villi, as changes in IGFBP-2 and IGFBP-4 would modify IGF-I and IGF-II bioavailability. Hoeflich et al (1998) have shown that in HT-29 cells and in other colonic cancer epithelial cell lines that exogenous IGFBP-2 inhibits cell proliferation. Thus, it can be speculated that both IL-1 and IL-6, by lowering further IGFBP-2 and IGFBP-4, could increase the proliferation rate.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in IGFBP-2 and IGFBP-4 in response to changes in local cytokine concentrations could alter the process of maturation of the enterocyte moving from the crypt to the apex of the villi, as changes in IGFBP-2 and IGFBP-4 would modify IGF-I and IGF-II bioavailability. Hoeflich et al (1998) have shown that in HT-29 cells and in other colonic cancer epithelial cell lines that exogenous IGFBP-2 inhibits cell proliferation. Thus, it can be speculated that both IL-1 and IL-6, by lowering further IGFBP-2 and IGFBP-4, could increase the proliferation rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have reported that renal levels of IGFBP-2 protein increase with the onset of glomerulosclerosis [43,49], and circulating IGFBP-2 levels may also be increased in diabetes [32,54,55]. In addition, a host of studies support IGFBP-2 having anabolic actions in different experimental cell models, although in other cell models it has also been reported to exert inhibitory effects [47,[56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro studies and in vivo experiments in which IGFBP-2 has been overexpressed or genetically deleted suggest that IGFBP-2 may have dual roles in modulating IGF actions consistent with the model of IGFBP function. Overexpression of IGFBP-2 in cells in vitro has resulted in both increased and decreased growth (Hoflich et al, 1998, Hoeflich et al, 2000. When overexpressed in the circulation, IGFBP-2 inhibited growth in transgenic mice (Hoeflich et al, 1999(Hoeflich et al, , 2001.…”
Section: Discussionmentioning
confidence: 99%